Bahay ni lola Regal Films presents. - Dantes, Dingdong; Karylle; Romero, Gloria (Regal Films Production, 2005)
Rupert and Nina are a young recently married couple who couldn't be happier. He's zomming up the corporate ladder at the ad agency where he works, while she's a glowing lady who's just given birth to a beautiful baby girl.